Promoting patient utilization of outpatient cardiac rehabilitation: A joint International Council and Canadian Association of Cardiovascular Prevention and Rehabilitation position statement. (1st January 2020) - Santiago de Araújo Pio, Carolina; Beckie, Theresa M.; Varnfield, Marlien; Sarrafzadegan, Nizal; Babu, Abraham S.; Baidya, Sumana; Buckley, John; Chen, Ssu-Yuan; Gagliardi, Anna; Heine, Martin; Khiong, Jong Seng; Mola, Ana; et al.
Abstract: Background: Cardiac Rehabilitation (CR) is a recommendation in international clinical practice guidelines given its' benefits, however use is suboptimal. The purpose of this position statement was to translate evidence on interventions that increase CR enrolment and adherence into implementable recommendations. Methods: The writing panel was constituted by representatives of societies internationally concerned with preventive cardiology, and included disciplines that would be implementing the recommendations. Patient partners served, as well as policy-makers. The statement was developed in accordance with AGREE II, among other guideline checklists. Recommendations were based on our update of the Cochrane review on interventions to promote patient utilization of CR. These were circulated to panel members, who were asked to rate each on a 7-point Likert scale in terms of scientific acceptability, actionability, and feasibility of assessment. A web call was convened to achieve consensus and confirm strength of the recommendations (based on GRADE). The draft underwent external review and public comment. Results: The 3 drafted recommendations were that to increase enrolment, healthcare providers, particularly nurses (strong), should promote CR to patients face-to-face (strong), and that to increase adherence part of CR could be delivered remotely (weak). Ratings for the 3 recommendations were 5.95 ± 0.69 (mean ± standard deviation), 5.33 ± 1.12 and 5.64 ± 1.08, respectively. Conclusions: Interventions can significantly increase utilization of CR, and hence should be widely applied. We call upon cardiac care institutions to implement these strategies to augment CR utilization, and to ensure CR programs are adequately resourced to serve enrolling patients and support them to complete programs. Highlights: Cardiac rehabilitation (CR) is grossly under-utilized, despite its' proven benefits. A recently-updated Cochrane review established interventions to increase use. These were translated into implementable recommendations, using best practices. Implementation tools include an online course to educate inpatient care providers. Patient preferences and barriers should be considered to optimize use.